Developmental Morphology and Anatomy Shed Light on Both Parallel and Convergent Evolution of the Umbellate Inflorescence in Monocots, Underlain by a New Variant of Metatopy - Martínez-Gómez, Jesús; Atluri, Tara A. M.; Rose, Irving Jason; Holliday, Aaliyah J.; Strock, Christopher F.; Lynch, Jonathan P.; Miller, William B.; Stevenson, Dennis Wm.; Specht, Chelsea D. (Frontiers in Plant Science, 2022)
Inflorescence structure is very diverse and homoplasious, yet the developmental basis of their homoplasy is poorly understood. To gain an understanding of the degree of homology that these diverse structures share, we characterize the developmental morphology and anatomy of various umbellate inflorescences across the monocots and analyzed them in an evolutionary context. To characterize branching order, we characterized the developmental morphology of multiple inflorescences with Sattler’s (1968) method of epi-illumination, and vascular anatomy with Laser Ablation Tomography, a novel high-throughput method to reconstruct three-dimensional vasculature. We used these approaches to analyze the umbellate inflorescences in five instances of presumed homoplasy: in three members of the Amaryllidaceae; in three members of the Asparagaceae, including a putatively derived raceme in Dichelostemma congestum; in Butomus umbellatus (Alismataceae), in Tacca chantrieri (Dioscoreaceae), and in umbellate structure in Fritillaria imperialis (Liliaceae). We compare these with racemes found in three members of the subfamily Scilliioideae (Asparagaceae). We find there are three convergent developmental programs that generate umbellate inflorescences in the monocots, bostryx-derived, cincinnus-derived and raceme-derived. Additionally, among the bostryx-derived umbellate inflorescence, there are three instances of parallel evolution found in the Amaryllidaceae, in two members of Brodiaeoideae (Asparagaceae), and Butomus umbellatus, all of which share the same generative developmental program. We discuss the morphological modifications necessary to generate such complex and condensed structures and use these insights to describe a new variant of metatopy, termed horizontal concaulesence. We contextualize our findings within the broader literature of monocot inflorescence development, with a focus on synthesizing descriptive developmental morphological studies.